2005
DOI: 10.4049/jimmunol.174.10.6477
|View full text |Cite
|
Sign up to set email alerts
|

Human Lymphoid and Myeloid Cell Development in NOD/LtSz-scid IL2Rγnull Mice Engrafted with Mobilized Human Hemopoietic Stem Cells

Abstract: Ethical considerations constrain the in vivo study of human hemopoietic stem cells (HSC). To overcome this limitation, small animal models of human HSC engraftment have been used. We report the development and characterization of a new genetic stock of IL-2R common γ-chain deficient NOD/LtSz-scid (NOD-scid IL2Rγnull) mice and document their ability to support human mobilized blood HSC engraftment and multilineage differentiation. NOD-scid IL2Rγnull mice are deficient in mature lymphocytes and NK cells, survive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
1,437
9
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,540 publications
(1,492 citation statements)
references
References 73 publications
40
1,437
9
6
Order By: Relevance
“…It is reasonable to assume that similar distributions of V-J combinations in humans and humanized mice may translate into similar distributions of CDR3 sequences as well. However, previous work assessing CDR3 repertoire diversity by PCR spectratyping reported poor repertoire diversity in reconstituted NSG mice [4], in apparent disagreement with our hypothesis. A major difference, however, is that the whole spleen was subjected to CDR3 spectratyping in the former study whereas we sorted human CD3 1 cells before analysis for semi-quantitative PCR.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It is reasonable to assume that similar distributions of V-J combinations in humans and humanized mice may translate into similar distributions of CDR3 sequences as well. However, previous work assessing CDR3 repertoire diversity by PCR spectratyping reported poor repertoire diversity in reconstituted NSG mice [4], in apparent disagreement with our hypothesis. A major difference, however, is that the whole spleen was subjected to CDR3 spectratyping in the former study whereas we sorted human CD3 1 cells before analysis for semi-quantitative PCR.…”
Section: Discussioncontrasting
confidence: 99%
“…The extent of the human T-cell repertoire diversity generated in mice may represent an important functional indicator [3], useful for immunological studies in the models. However, although some studies have reported on the TCR repertoire diversity of humanized mice [4,5], a comprehensive analysis of T-cell repertoire combinatorial diversity in humanized mice is lacking. We believe that this analysis is relevant since it may provide new information about the rules governing V-J combinations distribution in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial limitations of the SCID and NOD-SCID mice for the implantation and long term survival of human normal and neoplastic tissues have now been overcome by the generation of a new generation of NOD-SCID mouse with a null mutation of the IL-2 common γ chain receptor [130][131][132]. These NOD-SCID IL2Rγ null mice are called NOG mice, and the IL-2R mutation results in a defect of the high affinity receptors for IL-2, IL-4, IL-7, IL-9, IL-15, and IL-21 that blocks the development of NK cells and further impairs innate immunity [130,133].…”
Section: Mouse/human Xenograft Models To Study In Vivo Dynamic Interamentioning
confidence: 99%
“…22 Aside from obviating the need for frequent injections of the NK mAb, these animals also support engraftment of other human cell lineages, in addition to T cells. 23 Identical adoptive transfers of PBMNCs (from the same healthy human donor as for the previous studies) into the NOD/SCID IL-2R␥ null resulted in enhanced engraftment and propagation of activated human T cells ( Figure 5, A and B), compared with the original NOD/ SCID animals ( Figure 1B). Donor human B cells (CD19 ϩ ), monocytes (CD14 ϩ ), and some macrophages (CD68 ϩ ) were also evident in the spleens of the NOD/SCID IL-2R␥ null recipients.…”
Section: Studies In Nod/scid Il-2r␥ Null Micementioning
confidence: 79%